Species richness, cultural importance, and prioritization of wild spices for conservation in the Sudano-Guinean zone of Benin (West Africa) - Konoutan Médard Kafoutchoni; Rodrigue Idohou; Anthony Egeru; Kolawolé Valère Salako; Clément Agbangla; Aristide Cossi Adomou; Achille Ephrem Assogbadjo (BMC, 2018)
Abstract Background Spices have always been used for their flavor-enhancement characteristics and for their medicinal properties. In Benin, scientific research on spices is scarce, despite their importance in the local population's daily needs. This study investigated the diversity of wild spices and documented the associated traditional knowledge that can be used for their valuation, domestication, and sustainable management in the Sudano-Guinean Zone of Benin. Methods Data were collected during field expeditions using semi-structured interviews in ten localities across the three phytodistricts of the zone. Species richness and Shannon's diversity index were estimated using species accumulation curves. Use report (UR), cultural importance, use value (UV) index, and informant consensus factor (F ic) were used to assess traditional knowledge on wild species, their local importance, and informants' agreement among sociolinguistic groups. Priority wild spices were finally identified using an approach combining eight criteria (native status, economic value, ethnobotanical value, global distribution, national distribution, in-situ and ex-situ conservation status, legislation, and threats assessment) in four prioritization methods (point scoring procedure, point scoring procedure with weighting, compound ranking system, and binomial ranking system). Results A total of 14 species, belonging to 12 genera and 9 families, were inventoried. The most prominent families were Zingiberaceae (21.43%), Annonaceae (21.43%), and Rutaceae (14.29%). More than 200 specific uses were reported, with the Tchabè people holding the greatest level of knowledge (70 uses; UR = 5.70 ± 0.33). The culturally most important spices differed among sociolinguistic groups. Most of the informants agree on the use of the species among (F ic = 0.72-0.98) and across the considered use categories (F ic = 0.88-0.99). The highest UV were registered for Aframomum alboviolaceum (UV = 0.93), Lippia multiflora (UV = 0.76), and Aframomum angustifolium (UV = 0.18). Overall, people perceived wild spices as declining due to agriculture, grazing, and drought. Five species, A. alboviolaceum, L. multiflora, Monodora tenuifolia, Xylopia aethiopica, and Z. zanthoxyloides, were the most prioritized for conservation. Conclusions This study provides information relevant for the implementation of conservation and domestication actions of wild spices in Benin. Priority species could be integrated into traditional agroforestry systems (e.g., home gardens). However, for this to be effective, further research should be undertaken on morphological and genetic diversity and propagation methods of priority wild spices.